Comparison of the power generating characteristics of KIST- and FZ-julich SOFCs - Jung, H.Y.; Lee, S.C.; Tietz, F.; Kim, H.-R.; Lee, H.-W.; Lee, J.-H. (Korean Ceramic Society, 2007)
We evaluate and compare the power generating characteristics of the anode supported SOFCs which have been fabricated from KIST and FZ-Julich in Germany. The performance and electrochemical property of each unit cell was characterized at the temperature range of 650-850°C under same operating conditions and its microstructural property was thoroughly investigated via SEM after the performance test. According to the investigation, KIST- and FZJ SOFC showed different power generating characteristics in their temperature dependances due to their different design of electrode microstructure, especially the cathode microstructure. FZJ SOFC showed better performance at high temperature while showed lower performance at lower temperature. From the investigation about the correlation between microstructure and electrochemical property, we found that the superior performance of FZJ SOFC at high temperature was mainly due to its lower cathodic polarization resistance whereas better performance of KIST SOFC at lower temperature was mostly attributed to the lower ohmic resistance.